A bimodal-pore strategy for synthesis of Pt3Co/C electrocatalyst toward oxygen reduction reaction. Issue 35 (6th April 2021) - Hong, Wei; Shen, Xinran; Wang, Fangzheng; Feng, Xin; Li, Jing; Wei, Zidong
Abstract : The Pt3 Co/C catalyst, with active Pt3 Co nanoparticles located around the mass transfer channels rather than inside them, leads to smoother mass transfer and better performance. Abstract : A bimodal-pore strategy was developed for preparation of the Pt3 Co/C catalyst with active Pt3 Co nanoparticles located around the mass transfer channels rather than inside them, which leads to ca. 29% higher mass transfer efficiency and a superior single-cell performance under an ultralow Pt loading.